1985
DOI: 10.4141/cjss85-061
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Ortho- And Polyphosphates in Some Quebec Soils as Affected by Added Organic Residues and Calcium Carbonate

Abstract: Al and Fe contents, but some significant curvilinear relationships were observed.The results indicate that PP and PolyN-P may be retained to a lesser degree than OP in soils dominated by sesquioxides of Fe and Al. Application of farmyard manure (FYM) and alfalfa residues reduced the retention of ortho-and polyphosphate in the surface soils. The magnitude of the effect was greater with FYM than with alfalfa residues. The results suggest that P uptake from added polyphosphate could be enhanced by added organic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Dormaar and Chang (1995) reported 15 to 46% of total P was present as water-extractable P i + P o and resin-extractable P i after 20 yr of cattle manure addition. MnKeni and McKenzie (1985) suggested that this is due to an important cumulative effect of manure additions and a decrease in soil P adsorption as fixation sites become saturated. In our Can.…”
Section: Effect Of Manure Application On Soil P Distribution Among Frmentioning
confidence: 99%
“…Dormaar and Chang (1995) reported 15 to 46% of total P was present as water-extractable P i + P o and resin-extractable P i after 20 yr of cattle manure addition. MnKeni and McKenzie (1985) suggested that this is due to an important cumulative effect of manure additions and a decrease in soil P adsorption as fixation sites become saturated. In our Can.…”
Section: Effect Of Manure Application On Soil P Distribution Among Frmentioning
confidence: 99%
“…Dormaar and Chang (1995) reported 15 to 46% of total P as water-extractable P i + P o and resin-extractable P i after 20 yr of cattle manure addition. MnKeni and MacKenzie (1985) suggested that this is due to an important cumulative effect of manure additions and a decrease in the soil P adsorption as fixation sites become saturated. In our study, the available phosphate in the liquid swine manure used was about 70% of the total P in the manure, which means most of P from the manure was labile.…”
Section: Effect Of Manure and Urea On Total P And P Fractions In Soilmentioning
confidence: 99%
“…Long-term manure addition has been known to increase the P i forms in the labile and moderately labile fractions and also to increase to total P content (MnKeni and MacKenzie 1985;Domaar and Chang 1995;Tran and N'dayegamiye 1995). Dormaar and Chang (1995) reported 15 to 46% of total P as water-extractable P i + P o and resin-extractable P i after 20 yr of cattle manure addition.…”
Section: Effect Of Manure and Urea On Total P And P Fractions In Soilmentioning
confidence: 99%
“…For manure applications to soil, the rate of change in extractable soil P forms depends on the soil characteristics, availability of the P in the manure, rate of P application, and the number of applications. A cumulative effect of manure applications is often observed and has been suggested to reflect the saturation of P fixing sites in the soil (MnKeni and MacKenzie 1985). Few studies, however, have examined the potential impact on crop production and changes in soil P forms and levels under conditions of reduced P inputs, as would occur if restrictions to P applications were suggested by a P index.…”
Section: Introductionmentioning
confidence: 99%